2022
DOI: 10.1136/gutjnl-2021-326269
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota regulate Alzheimer’s disease pathologies and cognitive disorders via PUFA-associated neuroinflammation

Abstract: ObjectiveThis study is to investigate the role of gut dysbiosis in triggering inflammation in the brain and its contribution to Alzheimer’s disease (AD) pathogenesis.DesignWe analysed the gut microbiota composition of 3×Tg mice in an age-dependent manner. We generated germ-free 3×Tg mice and recolonisation of germ-free 3×Tg mice with fecal samples from both patients with AD and age-matched healthy donors.ResultsMicrobial 16S rRNA sequencing revealed Bacteroides enrichment. We found a prominent reduction of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 77 publications
3
94
0
Order By: Relevance
“…Many studies have shown that the gut microbiota plays an important role in aging-related diseases and unhealthy aging. For example, gut dysbiosis contributes to Alzheimer’s disease pathologies by enhancing neuroinflammation and regulating microglia activation in the brain ( Chen et al, 2022 ); age-related changes in the gut microbiota influence systemic inflammation and stroke outcome ( Spychala et al, 2018 ). Transplantation of gut microbes from aged mice to adult mice induces an obese phenotype, promotes inflammatory responses, impairs spatial memory and learning ability, and causes an aging phenotype in adult mice, suggesting the possibility of adaptive changes in gut microbiota in response to the aging process and the possibility of life extension by modulating the gut microbiota ( Finlay et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the gut microbiota plays an important role in aging-related diseases and unhealthy aging. For example, gut dysbiosis contributes to Alzheimer’s disease pathologies by enhancing neuroinflammation and regulating microglia activation in the brain ( Chen et al, 2022 ); age-related changes in the gut microbiota influence systemic inflammation and stroke outcome ( Spychala et al, 2018 ). Transplantation of gut microbes from aged mice to adult mice induces an obese phenotype, promotes inflammatory responses, impairs spatial memory and learning ability, and causes an aging phenotype in adult mice, suggesting the possibility of adaptive changes in gut microbiota in response to the aging process and the possibility of life extension by modulating the gut microbiota ( Finlay et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although AD has traditionally only been studied from a neurological perspective, recent works implicate an immune and microbial basis in the development of the disorder. GF and ABX mouse models for AD are protected from Aβ plaque aggregation and neuroinflammation [93,94] . Furthermore, transgenic AD mice compose a distinct microbiome from their wildtype counterparts, with AD-associated microbiomes shifting with age and disease progression [2] .…”
Section: The Gut Microbiota On Microgliamentioning
confidence: 99%
“…In all of these individual studies, the microglia is the mechanism tying the microbiota with AD. Microglia of GF and ABX-treated AD mice have better recruitment and uptake of Aβ deposits, as well as reduced inflammatory phenotypes [2,94] . This may be attributed to microbial metabolite profiles in AD patients.…”
Section: The Gut Microbiota On Microgliamentioning
confidence: 99%
“…N-3 polyunsaturated fatty acids (PUFAs) are essential dietary nutrients and play central roles in learning, memory, and the regulation of the nervous and cardiovascular systems [ 16 ]. Chen et al reported that gut dysbiosis might contribute to the pathogenesis of AD by inducing PUFA-associated neuroinflammation [ 17 ]. PUFAs slowed the short-term progression of illness in mice with abnormal neuropsychiatric behaviours by indirectly elevating the release of neurotransmitters [ 18 ] and modulated lipid disorders in humans by increasing levels of glycine-conjugated hyodeoxycholic acid (a secondary bile acid with hypolipidemic properties) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%